Evaluation of the biological activity of the medicinal plant pata-de-vaca (Bauhinia forficata L.) against the bacterium Escherichia coli, using a flow injection analysis system - Ramos, Mateus Lima; Ramos , Isabela Mota; Vieira, Jonas Alves; Cunha, Ananda Helena Nunes; da Costa, Orlene Silva; Cordeiro, Lis Vieira; Cordeiro, Alice Alves (Seven Editora, 2023)
Plants for medicinal purposes are widely used worldwide for the treatment, cure and prevention of diseases. Among the numerous plant species of medicinal interest, the plants of the genus Bauhinia are cited a lot, which are normally found in the tropical areas of the planet, and have some important pharmacological activities, for example, hypoglycemic. The objectives of this work were: to evaluate the biological activity of the medicinal plant pata-de-vaca (Bauhinia forficata L.), against the bacterium Escherichia Coli using a flow injection analysis system, coupled with a spectrophotometer, and, in parallel, to carry out the research of secondary metabolites present in the leaves of this plant, through the so-called prospecting tests. Through this system, it was possible to observe its behavior against the bacteria E. coli. The present study demonstrated that there is a range of metabolites present in the leaves of Bauhinia forficata L., which may present significant pharmacological and biological activities. It was also found that there are indications that compounds present in this plant may favor, and others may inhibit, the proliferation of microorganisms, in theory the bacteria Escherichia coli. The ethyl acetate, hexane and aqueous fractions obtained from the crude ethanolic extract of the plant samples were used. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-074